STRATEGI MEMBANGUN LOYALITAS PELANGGAN MELALUI PENINGKATAN BRAND IMAGE PRODUK AMDK PADA AGEN XYZ - Oktaga, Andreas Tigor; Yoki Nawan Gunara; Umi Fadlilah Hidayanti (Jurnal Ilmiah Ekonomika & Sains, 2025)
This research analyzes the formation of AMDK customer loyalty through hyper-local promotion mediated by brand image at the local distributor agent level, aiming to fill a research gap previously focused at the corporate level. A quantitative approach was employed, with data analyzed using Structural Equation Modeling (SEM) to test the causal relationships between variables. The findings reveal that hyper-local promotion significantly shapes brand image (β=0.63), and brand image has a strong impact on customer loyalty (β=0.73). Brand image acts as a dominant partial mediator with a high Variance Accounted For (VAF) of 83%, while the direct effect of promotion on loyalty is small (β=0.27). The predictive power of the model is also strong, with an R2 for brand image at 0.62 and for customer loyalty at 0.68. The study's implications highlight a key strategy for distributors: building a strong agent-level brand image through integrated hyper-local promotion is crucial for achieving sustainable customer loyalty. Theoretically, this research enriches the existing literature on hyper-local marketing by providing empirical evidence of the mediating role of brand image at the micro level.